2019
DOI: 10.29137/umagd.385030
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Endüstri Mühendisliği Eğitiminin Mezun Görüşlerine Dayalı Analizi

Abstract: Öz Türkiye' de her yıl binlerce öğrenci farklı üniversitelerin endüstri mühendisliği bölümünden mezun olmakta ve çeşitli sektörlerde iş hayatına başlamaktadır. Öğrenciler, üniversitelerinden aldıkları eğitim ve vizyon sayesinde çalıştıkları sektörlerde başarılı olabilmektedir. Alınan eğitimlerin değerlendirilmesi ise ancak mezun olduktan sonra anlaşılabilmektedir. Bu çalışmada, Türkiye' de endüstri mühendisliği eğitimi veren üniversitelerin değerlendirilmesi ve karşılaştırılması için mezun görüşlerine dayalı b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Higher education institutions' activity about soft skills teaching has been in place as a controversial topic in literature (Nair, Patil and Mertova, 2009;Özsoy, 2013;Bayram, Çelik and Oral, 2015;Esa, Selamat, Padil, and Jamaludin, 2014;Naiem et al, 2015;Wilson and Marnewick, 2018;Uçar and İşleyen, 2019). These studies evaluating the opinions of students and graduates showed that course content doesn't meet adequately the knowledge and skills necessary for working life and that higher education institutions do not give enough importance to soft skills as much as technical skills.…”
Section: Proposed Approaches For Soft Skill Acquisitionmentioning
confidence: 99%
“…Higher education institutions' activity about soft skills teaching has been in place as a controversial topic in literature (Nair, Patil and Mertova, 2009;Özsoy, 2013;Bayram, Çelik and Oral, 2015;Esa, Selamat, Padil, and Jamaludin, 2014;Naiem et al, 2015;Wilson and Marnewick, 2018;Uçar and İşleyen, 2019). These studies evaluating the opinions of students and graduates showed that course content doesn't meet adequately the knowledge and skills necessary for working life and that higher education institutions do not give enough importance to soft skills as much as technical skills.…”
Section: Proposed Approaches For Soft Skill Acquisitionmentioning
confidence: 99%